Exploring and explaining participation in local opposition: brown coal mining in Horní Jiřetín - Černoch, Filip (Masaryk University Press, 2021)
This book summarizes a three-year research project on local opposition to coal mining in the Northwestern part of the Czech Republic. The research focused on the relational dimensions of the opposition movement and the political context in which the movement operates.